Peran Kepala Desa dalam Pengelolaan APBDes - Naila Aulia; Warsito Kawedar (WACANA EKONOMI (Jurnal Ekonomi, Bisnis dan Akuntansi), 2024)
The Ministry of Finance has recorded that the allocation of Village Funds from 2015 to 2022 has reached IDR 468.9 trillion. With the significant amount of village funds disbursed by the government to achieve community development targets, a top management figure with the ability to drive all success indicators is required. This study aims to analyze the role of the village head in managing the Village Revenue and Expenditure Budget (APBDes) with a case study in Kemambang Village, Banyubiru District, Semarang Regency. Using a qualitative approach, primary data were collected through in-depth interviews with village officials and community members knowledgeable about the village head's role. The findings reveal that the Village Head of Kemambang (2013-2019) is viewed as a reliable, creative, and innovative leader. The village head initiates the APBDes Plan through participatory involvement of various community layers, implements development via a self-management system, and ensures transparent and fair management of development projects. This leadership has earned respect from both officials and the community, and the village head regularly reports performance through village inspections and annual accountability reports to the government.